PRINCIPAL’S ORGANIZATIONAL MANAGEMENT AND THE IMPLEMENTATION OF ISLAMIC VALUE: A CASE STUDY IN SMP AL-AZHAR MANDIRI PALU - M.Pd., Mohamad Syafri (State Institute of Islamic Studies (IAIN) Palu, 2020)
The purpose of the study is to picture the role of school principal’s organizational management in implementing organizational communication and reward done in Al-Azhar Mandiri Palu Junior High School. The research also enpicture how school’s management could lead to beneficial effect, including the implementation of Islamic value. The method used in this research is qualitative method with in-depth interview, documentation, and observation as the instruments. The research was analyzed using data reduction, presentation, and verification. (1) The research showed that interpersonal communication is the main pilar in building the communication, those are supported with the use of communication technology and social networking efficiently and effectively. (2) The reward given to members of Al-Azhar Mandiri Palu are in form of intrinsic and extrinsic. (3) Despite the school’s status as a non-Islamic private school, but the school able to implement the Islamic value both for school’s members and activities. It also lead to some achievement in Islamic field.